Evangelizing Eugenics: A Brief Historiography of Popular and Formal American Eugenics Education (1908-1948) - Kohlman, Michael J. (Alberta Journal of Educational Research, 2013)
This article examines the history of the American Eugenics movement’s penetration into the formal and popular educational milieu during the first half of the 20th Century, and includes a review of some recent scholarly research on eugenic themes in education and popular culture. Apologists have dismissed the American Eugenics movement as a shortlived, racist, reactionary, and pseudoscientific aberration that was already dying long before the collapse of the Third Reich. Many official histories of biology and various social science disciplines including education were sanitized to expunge or trivialize the involvement of a host of important prophets, disciples, and evangelists in the eugenics movement. It was also common to divorce the research and statistical methods developed in the service of eugenics from their inspiration and original application to Galton’s secular religion of human betterment. In the last few decades, however, a new generation of scholars began to re-examine and illuminate the breadth and depth of the eugenics movement: its devotees and devotees’ actions and influence on their professions or academic disciplines and on society. These scholars also looked into how eugenics penetrated educational thought, curriculum, courses, and texts; thereby, revealing a panoply of overlapping interests, academic programs, organizations, and influential individuals that fatefully intersected and synergistically recombined into a powerful social movement throughout the first half of the 1900s. Cet article examine l’histoire de l’invasion des milieux formels et informels de l’éducation par l’eugénisme américain au cours de la première moitié du 20e siècle. On y présente également une brève étude de la recherche récente sur des thèmes portant sur l’eugénisme dans l’éducation et la culture populaire. Des apologistes ont écarté l’eugénisme américain en l’interprétant comme une aberration de courte durée, raciste, réactionnaire, pseudo-scientifique et qui était déjà moribonde bien avant l’écroulement du Troisième Reich. Plusieurs versions historiques officielles dans les domaines de la biologie et des sciences sociales, y compris l’éducation, ont été épurées de sorte à supprimer ou à banaliser l’implication d’une foule de prophètes, disciples et évangélistes importants dans le mouvement eugénique. Il était également courant de complètement séparer la recherche et les méthodes statistiques développées au service de l’eugénisme de leur inspiration et application originales puisées dans la religion séculaire de Galton visant l’amélioration de la condition humaine. Au cours des dernières décennies toutefois, une nouvelle génération de chercheurs ont commencé à examiner et à éclaircir la profondeur et l’ampleur de l’eugénisme en étudiant ses dévots, leurs actions et l’influence de ceux-ci sur leurs professions, leurs domaines académiques et la société. Ces chercheurs ont également étudié la pénétration par l’eugénisme de la pensée pédagogique, des programmes d’étude, des cours et des manuels, révélant ainsi une panoplie d’intérêts chevauchants, de programmes académiques, d’organismes et de personnages influents qui se sont recoupés de façon décisive et se sont recombinés par synergie en un puissant mouvement social pendant toute la première moitié du 20e siècle.